Prevalence and Clinical Profile of Drug Eruptions among Antiretroviral Therapy-Exposed HIV Infected People in Yaoundé, Cameroon - Emmanuel Armand Kouotou; Jobert Richie Nansseu; Vanessa Nancy Ngono; Sandra A. Tatah; Anne Cecile Zoung-Kanyi Bissek; Elie Claude Ndjitoyap Ndam (Hindawi Limited, 2017)
Background. Prevalence and incidence of drug eruptions vary around the world and are influenced by some key factors including HIV infection. Objective. This study aimed to find the peculiarities of drug eruptions in people living with HIV (PLHIV) and on antiretroviral therapy (ART). Methods. This was a retrospective cross-sectional study including ART-taking PLHIV, aged 15+ years, followed up between January 2010 and December 2014 at the day-care unit of the Yaoundé Central Hospital, and who presented with drug eruptions after ART initiation. Results. Of 6,829 ART-experiencing PLHIV, 41 presented with drug eruptions, giving a prevalence of 0.6%. The M/F sex ratio equaled 0.17. The mean age was 41.07 ± 11.36 years. Benign drug eruptions accounted for 83.3%. Milder forms were essentially maculopapular exanthema (36.6%), fixed pigmented erythema (7.3%), and urticaria (4.9%). Severe forms were represented by multiform erythema (4.9%), toxic epidermal necrolysis (2.4%), and drug hypersensitivity syndrome (2.4%). The Zidovudine + Lamivudine + Efavirenz ART-protocol was received by 48.8% of patients and 69% of patients were receiving Cotrimoxazole prophylaxis. Nevirapine, Efavirenz, Zidovudine, and Cotrimoxazole were suspected as the potential causes in 43.7%, 4.8%, 2.4%, and 26.8% of cases, respectively. Conclusion. Drug eruptions seem infrequent among ART-exposed HIV infected adult Cameroonians.